Витаминно-протеиновый продукт на основе селекционированных штаммов грибов: характеристика и применение - Супрун, С.М.; Донченко, Г.В.; Пархоменко, Ю.М.; Харкевич, Е.С.; Степаненко, С.П.; Лясота, В.П.; Сидниченко, И.В.; Кучмеровская, Т.М. (Фактори експериментальної еволюції організмів, 2013)
Aim. Morphological, physiological and biochemical properties of select strain mycelial fungi-producing protein, vitamins, co-enzymes were studied. Results.It was established that strains of Fusarium sambucinum F-10011F F-139 have a high growth rate of 0,28–0,34 hour 1, rich in essential amino acids, unsaturated fatty acids such as oleic, linoleic, linolenic and arachidonic. Especially valuable presence in fungi arachidonic acid, which is a precursor of prostaglandins in the body of animals and human, was found. The biotechnology of biopreparation based on physiology-biochemical properties was developed using joint cultivation of Fusarium sambucinum selected strains. This approach allowed reduce the terms of fermentation and increase the output of biologically active substances. The preparation includes hight content of vitamines, unsaturated fatty acids and other biologically active substances. The results of preclinical testing of fungal product have revealed a positive impact not only the growth of living biomass of warm-blooded animals, but also an increase antibacterial and lysotsyme actitvities of blood serum that led to increase of juveniles survival. Conclusions. Findings suggest the possibility to apply the developed vitamin-protein product for improvement enterprise performance and the natural resistance movement of farm animals for preparation fungal-producing drugs.